Study of changes in color characteristics of steel under thermal exposure - A. S. Gorbunov; M. V. Elfimova; Yu. N. Bezborodov (Омский научный вестник)
The article presents the results of studies of steel samples under thermal exposure, by measuring color characteristics using a model of color decomposition into RGB components. The data obtained can be used in the investigation of fires at objects made of steel building structures and objects made of steel. Thus, the specialist will be able to confirm his conclusions regarding the establishment of the source of the fire and the ways of its spread.